Análise dos resultados do SAEPE da disciplina de matemática dos 9.os anos do ensino fundamental - Gonçalves, João Baptista (2019)
Given the emphasis that external assessments have had over the past two deca des, both nationally and internationally, we feel the need to know them better to deepen our understanding of their real in uence on the educational environment. We were therefore looking for the origin of educational assessments, their develop ment and their modalities. We realize the concern of governments, international organizations and development banks to not only universalize access to basic edu cation, but also that all citizens have quality education. We have found large-scale assessment to be the primary instrument that governments and agencies have found to diagnose student education and learning systems and thus provide e ective me ans for decision-making in educational public policy. That said, it was necessary to understand the methodology of the large-scale evaluations, their preparation and execution stages as well as to understand how the sourced data are consolidated. We also investigated the possibilities of using these assessments as aids in the planning of educational networks. We seek curious to get to know more closely two exter nal evaluation models, SAEB and PISA, national and international, respectively, to better measure their contributions to state assessment systems. Finally, we focus on the e ort to contextualize the creation of the external evaluation System of the State of Pernambuco (SAEPE) and the transformations that occurred as a result of its implementation in a state school system. We conclude that the indices gene rated by these external evaluations do not reliably re ect the reality of the quality of education o ered in the studied school unit and would need to be discussed with the school community to provide collective decision making that would improve the quality of education.